The Effect Of Social Economic Changes During Pandemic COVID-19 Toward Child Wellbeing: a systematic literature review - Nurfurqoni, Fuadah Ashri; Kumoro, Retno; Siroj, Eko Yuliarti; Riany, Yulina Eva (Poltekkes Kemenkes Yogyakarta, 2023)
Pandemic Covid-19 has had a broad impact on human life; various restrictions cause various socioeconomic changes in family life, affecting the child's wellbeing. In contrast, the child's wellbeing must be adequately fulfilled so they can grow and develop into quality human resources. The purpose of this paper was to systematically review the evidence on the impact of socioeconomic changes during the pandemic on children's wellbeing. This systematic review was carried out following PRISMA guidelines. Data collection was carried out on March 18, 2022, using the Pro-Quest, Tailor and Francis, Emerald, Sage Pub, and Science Direct databases. Based on this study's exclusion and inclusion criteria, there were 19 studies included in this paper. The analysis results show that most of the included studies prove that socioeconomic status affects children's wellbeing, while one study showed that there is no effect. In conclusion, the findings from the review may provide guidelines for promoting better child wellbeing during the pandemic Covid-19.